KAJIAN PERKUATAN STRUKTUR GEDUNG YANG DISESUAIKAN DENGAN SNI GEMPA 03-1726-2012 KOTA SEMARANG STUDI KASUS GEDUNG KULIAH UTAMA FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Bayu Dwi Satrio; Gema Putra Pratama; Sri Tudjono; Hardi Wibowo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The Main Lecture Building of Engineering Faculty of Diponegoro University construction process start form June 2010 and be expected to finish at November 2010 but until October 2015 this building can not used as it planned because the construction process have some trouble. Design of this building still use the old guidence that is Earthquake SNI 03-1726-2002. This day that guidence has been updated become Earthquake SNI 03-1726-2012. Because of that this building need to studied so the building can accord with the new guidence. The purpose of this study is to design the structure strengthening so the building can accord with the new guidence. The method of this study is collect the data of laboratory examination. This data will use to determine the quality of materials for calculate nominal capacity. Then redesign the structure using SAP 2000 so that we can know the forces in every element of this structure. Then compere these forces with nominal capacity of the existed structure which is manually calculate under guidence of Concrete SNI 03-1726-2013. If the forces from SAP 2000 analysis bigger than the nominal capacity then the element need strengthening. The reviewed element are beam, column, joint and caisson foundation with strengthening use fiber reinforced polymer under guidence of ACI 440 and concrete jacketing. The result of analysis based on Earthquake SNI 03-1726-2012 show that some element in this building can not hold the forces. Beam can not hold the shear forces. Because of that, beam need the FRP shear strengthening to increase the nominal capacity. Beside beam, column also can hold the forces there are axial and moment. Because of this column need to use the concrete jacketing method to increase the nominal capacity. Concrete jacketing method more efficient than FRP strengthening for column.